Pengaruh good governance, pengendalian intern, dan budaya organisasi terhadap kinerja pemerintah daerah (studi pada satuan kerja pemerintah kabupaten pelalawan) - Ira Amelia; Desmiyawati '; Nurazlina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at the empirical evidence the influence of good governance, internal control, and organizational culture on government performance . This study uses a survey of the local unit Pelalawan .The samples used were as many as 126 people are respondents . The population in this study is 32 working units Pelalawan district . The type of data used is primary data by using questionnaire method of data collection . The method of data analysis used in this study is multiple regression ( multiple regression ) with the help of software SPSS version 17.0 .The results showed that good governance affect the performance of local governments with a regression coefficient of 0.999 with 0.000 significant ( alpha 0.05), , internal control affect the performance of local governments with regression coefficient 0.769 with a significant 0.000 ( alpha 0.05 ) , and culture organizational not influence on the performance of local governments with regression coefficient of -0.136 to 0.146 significant ( alpha 0.05) . R-square value is equal to 0.732 which means that 73.2 % of the independent variables in this study were able to influence the dependent variable . While the remaining 26.8 % is explained by other variables that are not included in this study such as organizational commitment , leadership style , and the other as his motivation . The influence of good governance , internal control , and organizational culture simultaneously significant effect on government performance .Keywords: good governance, internal control, organizational culture, local government performance.